The Effect of a Character Education Program on Moral Development and Self-Esteem of At-Risk Youth (Journal of Applied Juvenile Justice Services, 2021)
The purpose of this study was to examine the results of a psychological and educational intervention with at-risk youth that could benefit from a character education program. All sessions and material used focused on improving moral development and possibly self-esteem in each child. In summary, the findings did not support the use of the present character education intervention with the targeted population sample. The study did provide encouragement to continue to design and investigate programs that could possibly benefit at-risk youth. Ancillary data was also discussed concerning the issue of a false sense of high self-esteem in at-risk youth. Implications for counselors are also discussed.